Institutional infrastructure providing of stability of public finances: to raising of problem - Хмельков, Андрей Владимирович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
A problem, related to stability of public finances, rises in the article. The decision of the indicated problem is see the presence of institutional infrastructure which would provide the sought after stability to the research object.